2022
DOI: 10.3390/agronomy12040884
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Intraspecific Variability and Diversity in African Yam Bean Landraces Using Agronomic Traits

Abstract: Landraces are repositories for potential beneficial traits which could be used to develop varieties with enhanced qualities. Optimal utilization of the available large collection of landraces of African yam bean (AYB) presently conserved at the Genetic Resource Center, International Institute of Tropical Agriculture, Ibadan (GRC-IITA), requires an assessment of the magnitude and nature of genetic diversity within the germplasm. One hundred and ninety-six AYB accessions were evaluated during the 2018 and 2019 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…The principal component (PC) showed that the first four PCs accounted for 75.54% of the total variation. A similar result was reported by Olomitutu et al (2022) who obtained 70.2% of the variation in the first four principal components in AYB lines. The relative discriminating power of the PCA determines character contribution to the total variation, and its discriminating power is dependent on the strength of the axis as measured by their eigenvalues (Idehen et al, 2016;Akinyosoye et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The principal component (PC) showed that the first four PCs accounted for 75.54% of the total variation. A similar result was reported by Olomitutu et al (2022) who obtained 70.2% of the variation in the first four principal components in AYB lines. The relative discriminating power of the PCA determines character contribution to the total variation, and its discriminating power is dependent on the strength of the axis as measured by their eigenvalues (Idehen et al, 2016;Akinyosoye et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…significant and positive correlation recorded between pair of seed yield and other agronomic characters suggests that these traits could be governed by similar genes with pleiotropic effect or closely linked genes (Brown and Caligari, 2008). The significant and positive correlation between yield-related traits suggested that the traits could be improved simultaneously (Olomitutu et al, 2022). Hence, any of these characters could be used in indirect selection to increase yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The germplasm consisted of 196 AYB accessions obtained from the existing collection of landraces at the Genetic Resource Center, International Institute of Tropical Agriculture, Ibadan, Nigeria. The passport data of the accessions can be found in Olomitutu et al [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The seed contains 22.5% protein, 53.7% carbohydrate, and 3.6% crude fat content [ 7 ]. Despite its numerous other benefits, low seed yield is one of the major constraints to its production [ 8 , 9 ] due to the absence of improved varieties and a lack of significant research attention.…”
Section: Introductionmentioning
confidence: 99%